A Comparative Study of Mysore University and Karnatak University In S&T: Research Output, Citation Impact and Collaboration During 2001-10 - Kumbar, B. D.; Gupta, B. M. (Journal of Information and Knowledge, 2013)
The study provides a comparative assessment of the research contribution of the Mysore University and the Karnatak University in terms of publications output in science and technology, its growth and citation impact during 2001-10. It analyses the strong and weak subject areas of universities research and their citation impact. It describes the international collaborative share of research output of the universities at the overall level, indicating the contribution of the major collaborating partner countries. It also provides analyses of the national collaborating links of the two universities; with a view to study their collaborating linkages with academic institutions, institutes of national importance, research institutions and industry. It also studies the contribution and citation impact of the top 15 most productive authors and also the productivity of their most productive journals, where the two universities authors have published.